TLR9 agonist adsorbed to alum adjuvant prevents asthma-like responses induced by Blomia tropicalis mite extract. Issue 3 (22nd July 2019) - Nunes, Fernanda P B; Alberca-Custódio, Ricardo Wesley; Gomes, Eliane; Fonseca, Denise M; Yokoyama, Nicole H; Labrada, Alexis; Russo, Momtchilo
Abstract: Blomia tropicalis mite is highly prevalent in tropical and subtropical regions and it is associated with allergic diseases such as rhinitis and asthma. By using an OVA-model of allergic lung disease, we have previously shown that sensitization in the presence of toll like receptors (TLRs) agonists attenuates subsequent OVA-induced allergic responses. Here, we evaluated the effect of CpG-ODN, a specific synthetic TLR-9 agonist, on the development of experimental asthma induced by Blomia tropicalis extract, a relevant source of aeroallergens. Among different protocols of Blomia tropicalis extract sensitization, the subcutaneous sensitization in the presence of alum adjuvant induced the highest Th2 responses, including high IgE levels. Adsorption of CpG to Blomia tropicalis extract/Alum attenuated the airway hyperreactivity, the infiltration of inflammatory cells including eosinophils, and the IL-5 content in BAL. In addition, lung peribronchial inflammatory infiltrate, mucus production and IL-5-producing CD3 + CD4 + T cells were significantly reduced in the Blomia tropicalis extract/Alum+CpG group. Importantly, CpG inhibited total IgE production as well as active systemic or cutaneous anaphylaxis reactions. Inhibition of pulmonary Th2 responses was associated with increased IL-10 production but not with IFN-γ production. Notably, in IL-10-deficient mice, sensitization with OVA/Alum+CpG resulted in intense lung neutrophilia and IFN-γ production, indicating that IL-10 is necessary to inhibit subsequent Th1 immunity. Our work highlights the mechanisms of allergy attenuation by CpG and it indicates the potential use of Alum-based formulation with CpG to treat allergic processes. Graphical Abstract: CpG dampens allergic responses induced by Blomia tropicalis HDM extract . Sensitization to Blomia tropicalis house dust mite (HDM) with CpG adsorbed to alum adjuvant prevents the development of HDM- Blomia tropicalis -induced allergic lung inflammation and anaphylactic Ab production.